Trunk muscle endurance, flexibility, stride foot balance, and contralateral trunk lean in collegiate baseball pitchers - Myrick, K. M.; Pallone, A. S.; Feinn, R. S.; Ford, K. M.; Garbalosa, J. C. (The Journal of Strength and Conditioning Research, 2019)
The incidence of shoulder and elbow injuries in baseball is increasing. The trunk is crucial to transmission of energy from lower limbs, achieving the largest angular momentum and torque during pitching, and controlling acceleration of the arm. Excessive contralateral trunk lean has been correlated with increased ball velocity and forces on the elbow. Underlying biomechanical causes contributing toward excessive lean have not been well described. Previous studies outlined the importance of trunk muscle strength and endurance. Understanding contributing factors associated with contralateral lean and pitch velocity may be helpful in pitching performance, informing strength and conditioning protocols, and preventing injuries. The aim of this study was to examine the correlation between trunk muscle endurance and flexibility, and stride foot balance with contralateral lean during pitching. Level of significance was set at p < 0.05. Pitching motion analysis and functional assessments were obtained. Three-dimensional motion analysis was used. Average degree of contralateral lean was 2.33° (SD = 3.66). No statistically significant relationships were identified between trunk muscle endurance, flexibility, and stride foot balance with contralateral lean; moderate negative association between contralateral lean and pitch speed (B = 0.631, p = 0.175) was identified along with negative association of ipsilateral maximum trunk rotation (r = 0.108, p = 0.208) and ipsilateral side plank (r = 0.095, p = 0.194) with contralateral lean. Contralateral lean does not appear influenced by trunk muscle endurance, flexibility, or stride foot balance, and does not increase pitch velocity in high velocity pitchers. Future study is warranted to determine why contralateral lean exists at lower pitch velocities, and not at higher velocities.